2016
DOI: 10.1080/01446193.2016.1151063
|View full text |Cite
|
Sign up to set email alerts
|

The role of environmental sustainability in marketing of small architectural design practices

Abstract: Environmental sustainability in construction is a pressing concern. Despite their importance to the industry, and evident differences from large organisations in business strategy, markets and challenges, the literature has little to say about how small architectural design firms view the marketing potential of improved environmental sustainability. The current study aimed to address this gap, by examining practitioner experience of sustainability and marketing in small architectural design practices. Semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…As 14 of the participants were owner-managers of small firms, it could be expected that business development through incorporation of sustainable design could act as an extrinsic motivator. However, a separate analysis of marketing strategy by the firms here concluded that most failed to recognize the marketing potential of sustainable design (Murtagh et al, 2016) and none made reference to marketing, business or financial benefits of sustainable design.…”
Section: Paymentioning
confidence: 85%
See 1 more Smart Citation
“…As 14 of the participants were owner-managers of small firms, it could be expected that business development through incorporation of sustainable design could act as an extrinsic motivator. However, a separate analysis of marketing strategy by the firms here concluded that most failed to recognize the marketing potential of sustainable design (Murtagh et al, 2016) and none made reference to marketing, business or financial benefits of sustainable design.…”
Section: Paymentioning
confidence: 85%
“…Although quality of product lends itself to commercial value (Baker and Lamb, 1994), here the participants' focus was specifically on design rather than quality as a marketing strategy. Indeed, a separate analysis of marketing strategy by the firms who participated in this study found that most failed to recognize the marketing potential and actual marketing role of sustainable design in their business development (Murtagh et al, 2016). Given the emphasis in architectural education on the Vitruvian ideals of designing for soundness, usefulness and beauty, perhaps unsurprisingly, a number of participants linked high quality in design with sustainability, suggesting that pursuit of design quality is congruent with pursuit of improved sustainability.…”
Section: Discussionmentioning
confidence: 98%
“…The broader picture of how BCSs operate in their day-to-day activities is necessary alongside examining aspects relating to sustainability. 14 The term 'sustainability' has been critiqued as ill-defined (Murtagh, Roberts, & Hind, 2016). To ground references to sustainable construction in the analysis below, we begin with a brief summary of responses when participants were asked what they understood by "sustainable construction".…”
Section: Resultsmentioning
confidence: 99%
“…It encompasses numerous assessment criteria including comfort, space, energy, materials, water, and project delivery; however, it also prioritises energy performance (Awadh, ). Engagement with BREEAM is voluntary; however, it is often required by institutional policy (Parker, ) or local authorities in certain contexts (Murtagh, Roberts, & Hind, ). Although implementation may be challenging in smaller projects, these standards have nevertheless shaped the discourse on sustainable building in the United Kingdom (Murtagh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Engagement with BREEAM is voluntary; however, it is often required by institutional policy (Parker, ) or local authorities in certain contexts (Murtagh, Roberts, & Hind, ). Although implementation may be challenging in smaller projects, these standards have nevertheless shaped the discourse on sustainable building in the United Kingdom (Murtagh et al, ).…”
Section: Introductionmentioning
confidence: 99%